Pengaruh Supervisi Kepala Sekolah dan Motivasi Kerja Guru Terhadap Kualitas Pembelajaran Guru: Sebuah Systemic Lierature Review - Riyadi Riyadi (Journal of Innovation in Teaching and Instructional Media, 2025)
The quality of learning is a key indicator in determining the success of the educational process, especially at the elementary school level. Various factors contribute to the quality of learning, among them the strategic role of the principal in conducting academic supervision and the level of teacher work motivation. This article aims to analyze the influence of principal supervision and teacher work motivation on the quality of learning through a Systematic Literature Review (SLR) approach. This method is used to identify, assess, and synthesize the results of previous research relevant to the topic, with a publication range from 2019 to 2025. The search process for articles was conducted through Google Scholar using the keywords ‘the influence of principal supervision’, ‘teacher work motivation’, and ‘quality of learning’. The results of the study indicate that academic supervision carried out systematically, continuously, and participatively can enhance the professionalism and performance of teachers in learning. On the other hand, high work motivation of teachers, both intrinsic and extrinsic, significantly influences the improvement of work ethic, creativity, and enthusiasm in managing learning. Both complement each other and provide a real contribution to the improvement of the quality of learning. This research is expected to serve as a reference in formulating educational management strategies, especially in efforts to develop teachers and improve the quality of education in elementary schools.